The Relationship between intellectual capital and innovation : a review - Karchegani, Mohammad Rahmani (2013)
There are many factors that influence firm performance. In order to sustain competitive advantage and increase performance, firm needs to offer high-quality products at low cost. Many firms have responded to these competitive demands by being innovative in their practices and have shown enough flexibility to meet the expectations of their stakeholders. Economists assert that intellectual capital (IC) is a vital asset that helps organizations to create value in present economic syndrome and enables the organizations to be innovative. IC can boost the organizational performance through knowledge, experiences, skills of employees and also by defining new methods of task performance and being innovative in their processes. Thus, IC of a company indicates the value of ideas and capability of being innovative for a longer period. Many authors have examined the relationship between IC and firm performance. Their finding indicates the existence of positive and significant relationship and this inspires the idea to review the literature on the relationship between innovation and intellectual capital, the topic of this paper.